A Rare Benign Tumor With Diagnostic Difficulties: Synovial Chondromatosis - Oya ÜMİT YEMİŞÇİ,; Selin OZEN,; Hamide KART KÖSEOĞLU, (Archives of Rheumatology, 2020)
In this article, we present a case of a 47-year-old male patient presenting with an insidious onset of hip pain and loss of range of motion. The patient was initially treated conservatively to no avail. Detailed investigations included magnetic resonance imaging of the left hip which revealed a synovitis. Blood results were unremarkable apart from moderately raised inflammatory markers. Differential diagnoses of both intra- and extra-articular hip pain were ruled out and the patient treated for a preliminary diagnosis of psoriatic arthritis for a total of six months. Persistent pain resulted in a re-visit of the diagnosis and further clinical evaluation. This time, an X-ray of the hip revealed calcification at the joint. A computed tomography followed and revealed synovial thickening and intra-articular calcification. A biopsy was consistent with primary synovial chondromatosis (SC). Open synovectomy was performed approximately one year after the onset of symptoms. This case emphasizes the importance of re-visiting initial evaluations and diagnoses when faced with a difficult case of persistent hip pain so to avoid misdiagnosis and unnecessary pharmacological treatment. In view of its rarity and diagnostic challenges, future work on SC should concentrate on gathering data which can be used to produce a diagnostic algorithm.